2018
DOI: 10.1038/s41598-018-24769-2
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of 179 miRNA Expression in Blood Plasma of Lung Cancer Patients and Cancer-Free Individuals

Abstract: Lung cancer is one of major cancers, and survival of lung cancer patients is dictated by the timely detection and diagnosis. Cell-free circulating miRNAs were proposed as candidate biomarkers for lung cancer. These RNAs are frequently deregulated in lung cancer and can persist in bodily fluids for extended periods of time, shielded from degradation by membrane vesicles and biopolymer complexes. To date, several groups reported the presence of lung tumour-specific subsets of miRNAs in blood. Here we describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 67 publications
1
28
0
2
Order By: Relevance
“…Our data showed that circulating plasma miRNA-17 and miRNA-222 expression levels were significantly higher in patients with NSCLC than those in healthy controls (P=0.000). In accordance with our findings, previous studies have shown that aberrant miRNA expression in NSCLC patients' blood and healthy individuals is powerfully associated with cancer development and progress (Xu et al, 2015;Zaporozhchenko et al, 2018;Yang et al, 2018;Liu et al, 2018;Liu and Wang, 2017). Contrary to such speculations, Li et al, (2013) have revealed that the expression of miR-17-5p is reduced in triple-negative breast cancer tissues and that it can suppress tumor progression through inhibition of ETV1 oncogene in triple-negative breast cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that circulating plasma miRNA-17 and miRNA-222 expression levels were significantly higher in patients with NSCLC than those in healthy controls (P=0.000). In accordance with our findings, previous studies have shown that aberrant miRNA expression in NSCLC patients' blood and healthy individuals is powerfully associated with cancer development and progress (Xu et al, 2015;Zaporozhchenko et al, 2018;Yang et al, 2018;Liu et al, 2018;Liu and Wang, 2017). Contrary to such speculations, Li et al, (2013) have revealed that the expression of miR-17-5p is reduced in triple-negative breast cancer tissues and that it can suppress tumor progression through inhibition of ETV1 oncogene in triple-negative breast cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Many miRNAs are known to be involved in oncogenesis, tumor progression, and metastasis by targeting tumor suppressors, oncogenes, or other proteins associated with disease progression or drug resistance [4][5][6][7][8]. Differential expression of miRNAs in biological fluids of patients with different cancers and healthy donors has been previously reported by many groups [7,[9][10][11][12][13][14][15]. Other reports also showed extracellular vesicles (EVs) and cell-free nucleoprotein complexes carry distinct populations of miRNA, and the content of these miRNA pools can be used to develop promising tools for PCa screening [16,17].…”
Section: Introductionmentioning
confidence: 91%
“…Serum miR-15b-5p/miR-146b-3p, miR-20a-5p/miR-146b-3p, and miR-19a-3p/miR-146b-3p ratios were validated as independent diagnostic biomarkers for discriminating between NSCLC and benign pulmonary nodules (AUC ranging from 0.72 to 0.85), whereas miR-15b-5p/miR-146b-3p, miR-20a-5p/miR-146b-3p, miR-20a-5p/miR-17-5p, miR-92a-3p/miR-20a-5p, miR-16-5p/miR-20a-5p, and miR-16-5p/miR-19a-3p efficiently discriminated NSCLC from pulmonary inflammation diseases (AUC ranging from 0.54 to 0.80) [123]. Similarly, a 10-miRNA ratio panel, composed of 14 plasma miRNAs, accurately discriminated between LC patients and healthy controls with an AUC of 0.98 [124]. The serum miR-223 + miR-145 + miR-20a panel also accurately discriminated NSCLC patients from healthy controls with an AUC of 0.88.…”
Section: Mirnas As Tumor Biomarkersmentioning
confidence: 99%
“…In conclusion, the 10 miRNA ratios [124] and the miR-183 + miR-19b panel identified LC patients with the highest accuracy [119], while the miR-152 + miR-148a + miR-148b + miR-21 panel [110] showed the highest ability in discriminating NSCLC patients from healthy controls. Notably, miR-125b was able to accurately discriminate among all NSCLC stages [73], whereas the miR-301 + miR-200b + miR-193b + miR-141 [107] and miR-125a-5p + let-7e + CEA panels [101] specifically distinguished early-stage NSCLC patients.…”
Section: Mirnas As Tumor Biomarkersmentioning
confidence: 99%